SUMO E3 Ligase PIASy Mediates High Glucose-Induced Activation of NF-κB Inflammatory Signaling in Rat Mesangial Cells - Wei Huang; Yaling Liang; Jianhua Dong; Luping Zhou; Chenlin Gao; Chunxia Jiang; Meijuan Chen; Yang Long; Yong Xu (Hindawi Limited, 2017)
Background. Sumoylation is extensively involved in the regulation of NF-κB signaling. PIASy, as a SUMO E3 ligase, has been proved to mediate sumoylation of IκB kinase γ (IKKγ) and contribute to the activation of NF-κB under genotoxic agent stimulation. However, the association of PIASy and NF-κB signaling in the pathogenesis of diabetic nephropathy (DN) has not been defined. Methods. Rat glomerular mesangial cells (GMCs) were stimulated by high glucose; siRNA was constructed to silence the expression of PIASy; the expression of PIASy, SUMO isoforms (SUMO1, SUMO2/3), and NF-κB signaling components was analyzed by Western blot; the interaction between IKKγ and SUMO proteins was detected by coimmunoprecipitation; and the release of inflammatory cytokines MCP-1 and IL-6 was assayed by ELISA. Results. High glucose significantly upregulated the expression of PIASy, SUMO1, and SUMO2/3 in a dose- and time-dependent manner (P<0.05), induced the phosphorylation and sumoylation of IKKγ (P<0.05), and then triggered NF-κB signaling whereas MCP-1 and IL-6 were released from GMCs (P<0.05). Moreover, these high glucose-induced effects were observably reversed by siRNA-mediated knockdown of PIASy (P<0.05). Conclusion. The SUMO E3 ligase PIASy mediates high glucose-induced activation of NF-κB inflammatory signaling, suggesting that PIASy may be a potential therapeutic target of DN.